The Development of Tethered Drone Station - Mohd Fauzi, Mohamad Fariz; RAHIM, MOHAMMAD ZULAFIF (Research Progress in Mechanical and Manufacturing Engineering, 2022)
A drone is a type of unmanned aerial vehicle (UAV) where the aircraft is flying without a human pilot on board. For a tethered drone, there will be a ground power station that enables the drone to fly with an ultimate flight duration. The tethered drone station is connected to the drone using a wire cord to supply the electrical energy. As the drone flying away, the tethered system is required to feed a longer wire to the drone. Although several tethered drones feeding system designs are available, those published patented, and no detailed explanation on the system programming. Hence, this study is conducted to self-develop a suitable system for the wire control mechanism. Few practically possible design concepts are introduced in this thesis. Using load feedback signal was selected as the best option to control the wire stretching and feeding mechanism. A complete design was produced, utilizing load cell as a sensor to provide load data as the input signal to the Arduino Uno microcontroller. Thresholds load conditions were programmed into the micro-controller for the decision-making process on the suitable motor response (retract or feeding rotation). In general, the response conditions are default motion is retracted motion until the motor undergoes the feeding motion when the load is higher than the second threshold. As the system validation, several threshold conditions in the range of 50N to 600N were tested at the end of this development process. From the analysis, the design was found able to provide suitable responses at accurate pre-set threshold conditions with the average percentage errors of 1.85 and 1.07 for the retract and release responses, respectively